Psicologia e dialética: um estudo sobre a aplicação do método dialético à pesquisa em psicologia - Monte, Jaime Bezerra do (2008)
The main objective of this work has been to investigate the influence of Karl Marx s dialectical method on Cultural-Historical Theory. The research consisted of investigating the history of psychology, its dichotomies, and theoretical and methodological oppositions. In addition, Vygotsky s views on psychology s crisis have served as the point of departure for the comprehension of the dialectical method in the field of psychology. We have tried and differentiated Marx s dialectics from other views on dialectics that have appeared throughout the history of philosophy, and we have conceptualized psychology s research method. The object of study of this work is a doctoral thesis in which the author identifies the application of the dialectical method and its articulation with Cultural-Historical Theory. This work is organized in the following way: a brief history of psychology; the research method; definition of the elements of Marxist dialectics; an outline of Cultural-Historical Theory as seen in Vygotsky, Leontiev and Rubinstein; presentation and analysis of the data; and conclusion